2019
DOI: 10.1002/chem.201983862
|View full text |Cite
|
Sign up to set email alerts
|

Frontispiece: Cuprophilic Interactions in and between Molecular Entities

Abstract: Chemical bonding is central to the study of chemistry, and is one of the key concepts in understanding material structures, properties, and reactions. In their Minireview on page 8936 ff., Y.‐C. Tsai et al. summarize hitherto existing findings of cuprophilic interactions within dimeric Cu complexes as well as copper chain complexes of up to six copper centers.. Different factors having an impact on these interactions, such as ligand scaffolds, the nature of the ligand donor atoms, or the coordination number ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…12 The intermetallic distance for the compound D is close to the upper limit of 2.8 Å, generally considered for cuprophilic interactions. 16,26 In compound C, the azido linkers are adopting a μ 1,1,3 coordination mode, with, on the one side, a semibridging nitrogen atom [Table 2, d(Cu2−N) = 2.096(3) Å and d(Cu1−N) = 2.146(3) Å] that connects the two Cu1 and Cu2 centers of the {Cu 2 (μ 2 -dppm 2 )} core and, on the other side, one nitrogen atom that is connected only to the Cu1′ ion [d(Cu1−N) = 2.114(3) Å; Figure 1a]. Therefore, the Cu1 metal centers present a distorted P 2 N 2 tetrahedral coordination sphere, while the Cu2 centers have a distorted P 2 N 1 O 1 tetrahedral coordination sphere (as a result of the weak coordination of a THF solvent molecule).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The intermetallic distance for the compound D is close to the upper limit of 2.8 Å, generally considered for cuprophilic interactions. 16,26 In compound C, the azido linkers are adopting a μ 1,1,3 coordination mode, with, on the one side, a semibridging nitrogen atom [Table 2, d(Cu2−N) = 2.096(3) Å and d(Cu1−N) = 2.146(3) Å] that connects the two Cu1 and Cu2 centers of the {Cu 2 (μ 2 -dppm 2 )} core and, on the other side, one nitrogen atom that is connected only to the Cu1′ ion [d(Cu1−N) = 2.114(3) Å; Figure 1a]. Therefore, the Cu1 metal centers present a distorted P 2 N 2 tetrahedral coordination sphere, while the Cu2 centers have a distorted P 2 N 1 O 1 tetrahedral coordination sphere (as a result of the weak coordination of a THF solvent molecule).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11−15 We observed that the typical labile, flexible, and low-directional coordination sphere of the Cu(I) ion, initially regarded a priori as strongly restrictive in conventional CDS chemistry, turned out to be very effective to conduct the selective preparation of polymetallic assemblies based on this ion. Thus, we described the selective preparation of the sterically constrained and highly emissive tetrametallic Cu(I) metallacycle B bearing cuprophilic interactions (Scheme 1; it is generally admitted that such interactions are characterized by intermetallic Cu(I)−Cu(I) distance below 2.8 Å 16 ) from the self-assembly reaction of the precursor A with cyanide connecting ligands. 12 This thermodynamically stable tetrametallic assembly presents multiple chelates and metallacycle subunits embedding Cu(I) ions, whose flexible coordination sphere geometry can be advantageously adapted to the topology constraints induced in such scaffolds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This suggests that short Cu•••Cu distances are a characteristic of μboryl complexes. 30 A reaction type associated with dicopper μ-boryl complexes is activation of the C(sp)−H bonds of terminal alkynes. 14,26 Under comparable conditions (Scheme 5, top), 4 and 5 reacted with phenylacetylene more rapidly than their DPFN analogues (100% conversion by 4 and 5 within 30 min and 3 h, respectively, compared to ca.…”
Section: ■ Results and Discussionmentioning
confidence: 99%